Prevalence and predictors of tobacco use among Bhutanese adolescents - Sonam Rinchen; Surasak Taneepanichskul; Namgay Dawa (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to examine the prevalence of tobacco use and associated factors influencing the use of tobacco among adolescents in a school setting. Design/methodology/approach - A cross-sectional descriptive study was conducted amongst Bhutanese adolescents studying at high schools in the district of Wangdue Phodrang in May 2016. A total of 378 eighth-grade students from four schools participated in the study. A self-administered questionnaire was used to collect data. Bivariate and multivariate logistic regressions were carried out to describe the predictors of tobacco use. Findings - Of the 378 student participants, 52.90 percent were girls and 47.10 percent boys. The age ranged from 11 to 19 years, and the majority lived in school hostels (82 percent). The prevalence of smoking was 10.80 percent while smokeless tobacco users constituted 11.10 percent in the month preceding the study. Gender, tobacco use by siblings and friends, ever having tried alcohol, consumption of alcohol in the last 30 days, previous experimentation with cigarettes/bidi and smokeless tobacco/baba (p-value <0.05) were significantly related to the use of tobacco among students. In multivariate analysis, tobacco use by friends (AdjOR=1.09; 95%CI=0.01-2.48), ever having tried alcohol (AdjOR=2.24; 95%CI=1.75-3.72), current alcohol use (AdjOR=2.63; 95%CI=1.52-4.31), experimentation with cigarettes/bidi (AdjOR =39.46; 95%CI=11.91-90.63) or with smokeless tobacco/baba (AdjOR=32.61; 95%CI=11.78-90.30) were observed as the strong predictors of current tobacco use among adolescents. Originality/value - These study results re-emphasized the rising public health concern of tobacco use among younger boys and girls. The findings may help the Bhutanese policy makers and managers to better understand the present situation of adolescent tobacco use and its associated determinants, and formulate appropriate tobacco control strategies for adolescents.